Guthrie card methylomics identifies temporally stable epialleles that are present at birth in humans - Beyan, Huriya; Down, Thomas A.; Ramagopalan, Sreeram V.; Uvebrant, Kristina; Nilsson, Anita; Holland, Michelle L.; Gemma, Carolina; Giovannoni, Gavin; Boehm, Bernhard O.; Ebers, George C.; Lernmark, Åke; Cilio, Corrado M.; et al. (Genome Research, 2012)
A major concern in common disease epigenomics is distinguishing causal from consequential epigenetic variation. One means of addressing this issue is to identify the temporal origins of epigenetic variants via longitudinal analyses. However, prospective birth-cohort studies are expensive and time consuming. Here, we report DNA methylomics of archived Guthrie cards for the retrospective longitudinal analyses of in-utero-derived DNA methylation variation. We first validate two methodologies for generating comprehensive DNA methylomes from Guthrie cards. Then, using an integrated epigenomic/genomic analysis of Guthrie cards and follow-up samplings, we identify interindividual DNA methylation variation that is present both at birth and 3 yr later. These findings suggest that disease-relevant epigenetic variation could be detected at birth, i.e., before overt clinical disease. Guthrie card methylomics offers a potentially powerful and cost-effective strategy for studying the dynamics of interindividual epigenomic variation in a range of common human diseases.
10.1101/gr.134304.111